Bilateral optic perineuritis: a rare manifestation of giant cell arteritis - case report and literature review - Madkhali, Jnadi; Aba Alkhail, Ahmed B.; Aldriweesh, Mohammed A.; Al Malik, Yaser (Frontiers in Ophthalmology, 2025)
BackgroundGiant cell arteritis (GCA) is a granulomatous vasculitis in older individuals that primarily affects medium-to-large vessels. Owing to the involvement of the ophthalmic arteries, GCA can lead to severe ischemic complications, including vision loss. Optic perineuritis (OPN) is characterized by inflammation around the optic nerve sheath and is a rare manifestation of GCA with diagnostic and therapeutic challenges.Case presentationThis case study reports a 75-year-old female presenting with subacute constitutional symptoms of fever and poor appetite with bilateral eye pain and visual disturbance. The patient had elevated inflammatory markers, specifically an erythrocyte sedimentation rate of 120 mm/h, with imaging findings consistent with bilateral OPN and temporal artery biopsy-proven GCA. Treatment with high-dose dexamethasone, followed by oral prednisolone and tocilizumab, led to symptomatic improvement in vision stabilization.ConclusionThis case highlights the importance of recognizing OPN as a possible manifestation of GCA. Although cases of OPN are mostly idiopathic, it can rarely represent the first manifestation of GCA. Therefore, prompt diagnosis through brain imaging and temporal artery biopsy is essential, and aggressive treatment with steroids is crucial for managing GCA-associated OPN to prevent irreversible vision loss.